Cross Operator Charging Station Access Simulator - Dwidharma Priyasta; Hadiyanto Hadiyanto; Reza Septiawan; Wahyu Cesar (TEKNIK, 2025)
The use of battery-based electric vehicles (KLBB) continues to increase, so the ease of using the Public Electric Vehicle Charging Station (SPKLU) infrastructure for recharging electric vehicle batteries must be considered to increase public confidence. One of the problems in using electric vehicles is the concern about long-distance travel (range anxiety) due to limited battery capacity and the minimal number of SPKLUs. This research aims to provide a tool to simulate cross-operator charging stations using the EV roaming method. In this approach, charging station users only need to be registered with one SPKLU operator to use other charging stations. This research develops a set of simulation models called the EV Roaming Simulator and simulates several EV roaming scenarios concerning the basic functionality of four state-of-the-art EV roaming protocols. The simulator consists of three Open Charge Point Protocol (OCPP)-based models: the Charge Point Model, the Central System Model, and the National Access Point Model, representing charging stations, central systems, and roaming hubs. The simulator is capable of executing the given EV roaming scenario. It has the potential to be further developed and used in developing various newly proposed EV roaming systems.